Practical Long‐Distance Measurement‐Device‐Independent Quantum Key Distribution By Four‐Intensity Protocol. Issue 12 (28th October 2021) - Hu, Xiao‐Long; Jiang, Cong; Yu, Zong‐Wen; Wang, Xiang‐Bin
Abstract: Quantum key distribution (QKD) can provide unconditionally secure private communication between two remote parties. The measurement‐device‐independent (MDI) QKD can remove all security loopholes in measurement devices. However, the large value of the observed error rate in X basis has severely limited its key rate. The four‐intensity protocol with fully optimized post data processing can improve the key rate and distance of MDI‐QKD effectively. In this paper, the four‐intensity MDI‐QKD protocol is reviewed. In the four‐intensity protocol, each of Alice and Bob uses one intensity in Z basis and three intensities in X basis (normally including one vacuum). This improves the number of effective bits in Z basis. The joint mathematical treatment for statistical fluctuation and the parameter scan pointing directly to the final key rate are applied to reduce the effect of statistical fluctuation. The double scanning method further improves the key rate and the secure distance of the four‐intensity protocol. These have greatly improved the performance of the protocol with finite‐key effects. So far, many MDI‐QKD experiments are based on the four‐intensity protocol. The successful results of these experiments have clearly shown the superiority of the four‐intensity protocol in practical long‐distance MDI‐QKD. Abstract : The measurement‐device‐independent (MDI) quantum key distribution (QKD) can provide unconditionally secure private communication and remove all security loopholes in imperfect measurement devices. The four‐intensity protocol with fully optimized post data processing can improve the key rate and distance of MDI‐QKD effectively. This review summarizes the developments of the four‐intensity protocol and shows the advantages of this protocol.